Design and implement of high gain and low noise neural amplifier using compensation techniques - N. Manikandan; S. Muruganand; K. Karuppasamy (Institute of Advanced Engineering and Science, 2019)
Electroencephalography is refer to record the electrical signal with respect to brain activity and its reliable EEG information, using this to diagnosis disorder and tumors. However the signal is very difficult to capture and processing due to so many parameter. Mainly this signal is very low range that from 0.1 to 100μv in and its bandwidth range from 1Hz to 100 Hz. So the signal has amplified by using linear and accurate digital program amplifier(PGA).This amplifier has been designed by using First stage amplifier with gain of 120dB with low output noise. The PGA is consists of OPAMPs the PGA change from 10 dB to 120dB.Inorde to optimized the linear and gain accuracy a new structure resister array is proposed high gain PGA. Hence the simulated result has shown it is promising to exhibit an amplifier with high performance biomedical application.